Tackling sexual violence at universities an international perspective - Towl, Graham J.; Walker, Tammi (New frontiers in forensic psychology, 2019)
"This is the only book to offer an international perspective on the incidence, reporting and impact of sexual violence at universities. Drawing on evidence from the UK, North America and Australia, it situates sexual violence in universities within a broader societal context, and argues that university communities are uniquely well placed to prevent sexual violence, as well as support those who report it. Examining both the psychological and structural challenges to reporting sexual violence, the book provides a set of recommendations that move beyond awareness campaigns to call for systems to be put in place whereby reports of sexual assault are handled promptly, fairly, and consistently"--